Implemantasi Data Akuntansi Menggunakan Zahir Accounting Pada Sekolah Mengemudi Ar’rahman Cabang Manggarai - Siti Faizah; Laila Ersa; Vivi Maria (Artikel Ilmiah Sistem Informasi Akuntansi, 2021)
Accounting data processing is one thing that is very important for the smooth running of the business because almost all activities and transactions are always related to accounting. The company which is engaged in the service of car driving course institutions in processing accounting data still uses a manual system with written records in books ranging from recording transactions to making financial reports, so that processing accounting data takes a long time, allows errors in recording, less accurate reports, delays in finding the required data and data storage that is less secure because it is easily damaged and lost. The data collection methods used in this research are observation, interviews and literature studies. Accounting data processing using Zahir Accounting Version 5.1 is the best solution to solve the problems that exist in this company and with the implementation of this software it can make it easier to record transactions to the presentation of financial statements so that they become more accurate, effective and efficient. In terms of data retrieval becomes easier and faster and data storage becomes more secure